2015
DOI: 10.1292/jvms.14-0413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sprayed hypochlorous acid solutions for their virucidal activity against avian influenza virus through <i>in vitro</i> experiments

Abstract: Hypochlorous acid (HOCl) solutions were evaluated for their virucidal ability against a low pathogenic avian influenza virus (AIV), H7N1. HOCl solutions containing 50, 100 and 200 ppm chlorine (pH 6) or their sprayed solutions (harvested in dishes placed at 1 or 30 cm distance between the spray nozzle and dish) were mixed with the virus with or without organic materials (5% fetal bovine serum: FBS). Under plain diluent conditions (without FBS), harvested solutions of HOCl after spraying could decrease the AIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…Indeed, there are many emerging pathogenic bacteria and viruses such as norovirus, influenza virus, coronavirus, etc. surrounding us Song et al, 2015, Hakim et al, 2015, Ishihara et al, 2015 In the past, millions have lost their lives due to the presence of pathogenic microorganisms in the daily environment. Of especial concern is the need to protect vulnerable children in local communities of African and south and east Asian countries where infectious diseases are endemic.…”
mentioning
confidence: 99%
“…Indeed, there are many emerging pathogenic bacteria and viruses such as norovirus, influenza virus, coronavirus, etc. surrounding us Song et al, 2015, Hakim et al, 2015, Ishihara et al, 2015 In the past, millions have lost their lives due to the presence of pathogenic microorganisms in the daily environment. Of especial concern is the need to protect vulnerable children in local communities of African and south and east Asian countries where infectious diseases are endemic.…”
mentioning
confidence: 99%
“…In the above equation, tpc is bacterial titer from an untreated sample in log 10 CFU/m l , whereas ta is the titer of recovered bacteria from treated samples. The inactivation rate was acceptable when the RF was greater than or equal to 3 [ 13 , 27 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has a high capacity for killing pathogens by irreversibly denaturing the critical components of cells, such as nucleic acids (DNA/RNA), mitochondria, enzymes and surface proteins [ 48 ]. Previously, we have reported that SAHW has a virucidal efficacy toward avian influenza virus (AIV) on surfaces [ 13 ] and Newcastle disease virus (NDV) in the air, along with confirmed safety for chicks [ 14 ]. In the present study, we evaluated sprayed SAHW for its efficacy in inactivating Salmonella Infantis and E .…”
mentioning
confidence: 99%
“…HClO solution at around pH 6, which is prepared by the addition of NaClO and HCl to sterile water or saline, has been demonstrated to have excellent in vitro bactericidal properties at lower concentrations 50 200 ppm than NaClO for gram positive bacteria such as S. aureus, B. cereus, and B. subtilis, as well as gram negative bacteria such as P. aeruginosa Hakim et al, 2015;Ono et al, 2012;Hao et al, 2013;Sakarya et al, 2014 . However, HClO readily reacts with various NH 2 or CHO-containing organic e.g., protein, amino acid, and carbohydrate and inorganic compounds, and it leads to the rapid consumption of HClO under organic matter contaminated environments Ishihara et al, 2017, Sato et al, 2018 .…”
Section: Fig 1 Antibacterial Activity Of Disinfectants Against Bath mentioning
confidence: 99%